2015
DOI: 10.1111/ajgw.12203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acetaldehyde addition on the phenolic substances and volatile compounds of red Tempranillo wines

Abstract: Background and Aims The introduction of controlled amounts of oxygen into red wines influences the composition of the phenolic substances and volatiles, and therefore the sensory properties of the wines. The main aim of this study was to evaluate the impact of a simulation of the micro‐oxygenation technique through acetaldehyde addition, on colour, and on the composition of phenolic substances and volatiles of Tempranillo wines after 12 months of bottle storage. Methods and Results The analytical and sensory d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Therefore, detection of gluconic acid allows estimation of the health status of the grape harvest and wine quality within the production cycle at a winery. OIV stated that levels of gluconic acid of 200–300 mg/L or lower indicates sound grapes, whereas levels up to 1.0 g/L indicate an initial stage of fungus infection [ 52 ]. The maximum level detected in our wines was 0.34 g/L in C16 wine.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, detection of gluconic acid allows estimation of the health status of the grape harvest and wine quality within the production cycle at a winery. OIV stated that levels of gluconic acid of 200–300 mg/L or lower indicates sound grapes, whereas levels up to 1.0 g/L indicate an initial stage of fungus infection [ 52 ]. The maximum level detected in our wines was 0.34 g/L in C16 wine.…”
Section: Resultsmentioning
confidence: 99%
“…Acetaldehyde is known to react to anthocyanins, flavanols and tannins to form ethyl-bridged polymeric pigments which have less astringency (Cheynier, Duenas-Paton, Salas, Maury, Souquet, Sarni-Manchado, et al, 2006;Vidal, Francis, Noble, Kwiatkowski, Cheynier, & Waters, 2004) and which become resistant to sulfite bleaching (Sheridan & Elias, 2015). According to recent data acetaldehyde may react not only to anthocyanidins, but to phenolic acids and flavonols (Aleixandre-Tudo, Lizama, Alvarez, Nieuwoudt, Garcia, Aleixandre, et al, 2016) or to catechin itself (Sheridan & Elias, 2016). The reaction of some of these ARPs with acetaldehyde is much faster than previously expected and takes places, albeit at lower rates, even in the presence of equimolar amounts of SO 2 (Sheridan & Elias, 2016).…”
Section: Initial Oxygen Consumption Rates (Ocrs) and Initial Wine Commentioning
confidence: 99%
“…Recent studies in our group and elsewhere have shown that exogenous acetaldehyde can be used to improve red wine color stability and astringency. The use of exogenous acetaldehyde provides benefits for the wine without the risks of reactive intermediates formed due to oxygen exposure. Adducts formed by acetaldehyde are found to be bridged by an ethylidene moiety (Figure ), , which can occur via C6 or C8 on the A-ring of the flavonoid molecule. Ethylidene-bridging reactions can involve tannins and anthocyanins to form modified tannins as well as polymeric pigments. , Bridged products from reaction with acetaldehyde have been found in red wine and in model wine systems, , and evidence for ethylidene-bridged products of native tannins has been observed indirectly by phloroglucinolysis; however, these compounds are difficult to observe without fragmentation during ionization for MS.…”
Section: Introductionmentioning
confidence: 99%